(Re)categorizing lexical encapsulation: an experimental approach [data] - Loureda Lamas, Óscar; Teucher, Mathis; Hernández Pérez, Celia; Cruz, Adriana (Universität, 2025)
Anaphoric encapsulation is a discursive mechanism by which a noun phrase recovers an explicature. This eye tracking study addresses the question of whether categorizing versus recategorizing encapsulation lead to different processing patterns. Results show that (1) encapsulating noun phrases are cognitively prominent areas, (2) recategorization is never less effortful than categorization, (3) the prominence and instructional asymmetry of the encapsulating noun phrase with respect to the antecedent is greater in cases of recategorizing encapsulation. Overall, encapsulating noun phrases initiate a complex cognitive operation due to the nature of their antecedent, which includes both encoded and inferred information. A distinctive processing pattern emerges for recategorizing encapsulating noun phrases: greater local efforts, due to the introduction of new information, do not result in higher total reading times. Beyond the introductory section, the structure of this study is as follows: Section 2 discusses the properties of categorizing and recategorizing mechanisms. Section 3 reviews experimental research on nominal anaphoric encapsulation in Spanish. Section 4 outlines the key aspects of the experimental design and execution. Finally, sections 5 and 6 present the results of the experiment and offer a theoretical discussion of the findings.